Puberdade em novilhas - Guerreiro, Vagner Jannuzzi [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The age which heifers reach puberty depend on factors like genetics, environment and nutrition. Puberty in heifers can be defined as the onset of reproductive competence, the ability to ovulate a fertile oocyte with an estrous behavior and development of a corpus luteum with normal lifespan. The metabolic signals that trigger puberty are not yet fully defined. In Brazil, where most beef cattle are zebu, the age at puberty is very advanced, mainly these animals are feed with a poor diet. Many researches are trying to discover the metabolic signals that trigger puberty and anticipate better economic return in breeding farms. It has been demonstrated that the cascade of endocrine events that culminate in puberty can be hastened by an alternative management scheme that involves increased nutrient intake between 3 and 7 months of life. Different diet concentrations, different products and by-products have been used in research to achieve puberty early (less than 300 days of age). The hormonal induction of puberty, especially with the use of progestagens, has been developed in heifers as an alternative tool to improve reproductive efficiency in herds, increasing the amount of pregnant heifers in breeding season

Puberdade em novilhas. Botucatu, 2009. 17p. Trabalho de conclusão de curso de graduação (Medicina Veterinária, Área de Concentração: Reprodução Animal) – Faculdade de Medicina Veterinária e Zootecnia, Campus de Botucatu, Universidade Estadual Paulista “Júlio de Mesquita Filho”. Resumo A idade em que novilhas atingem a puberdade depende de fatores genéticos, ambientais e nutricionais. A puberdade em novilhas pode ser definida como a manifestação da competência reprodutiva, com a capacidade de ovular um ovócito fértil, acompanhado de um comportamento estral e desenvolvimento de um corpo lúteo de vida normal. Os sinais metabólicos que desencadeiam a puberdade ainda não estão totalmente definidos. No Brasil, onde a maioria dos bovinos de corte é zebuína, a idade a puberdade é muito avançada, devido principalmente ao tipo de nutrição que esses animais recebem. Pesquisas na área de nutrição e reprodução têm sido desenvolvidas para descobrir esses sinais metabólicos que desencadeiam a puberdade e, principalmente, antecipála para melhor retorno econômico em fazendas de cria. Estudos mostram que uma alimentação diferenciada no período de 3 a 7 meses de idade pode antecipar a puberdade. Diferentes concentrações de dietas, produtos e subprodutos têm sido usados em pesquisas para atingir puberdade precoce (abaixo de 300 dias de idade). A indução hormonal da puberdade, principalmente com o uso de progestágenos, tem sido desenvolvida em novilhas como ferramenta alternativa para melhorar a eficiência reprodutiva em rebanhos, aumentando a quantidade de novilhas prenhes na estação de monta
Keywords: Bezerros; Puberdade